2D or Synthetic 2D? A Reader Study of Visualization of Amorphous Calcifications. Issue 1 (20th January 2022) - Renaldo, Andrew; Miller, Matthew; Caley, Matthew; Ganti, Ramapriya; Patrie, James; Rochman, Carrie; Nguyen, Jonathan V
Abstract: Objective: Some vendors have created algorithms that generate synthetic 2D (s2D) images from a digital breast tomosynthesis (DBT) dataset to reduce the radiation from obtaining a separate 2D digital mammography (DM). This study evaluated the visibility of amorphous calcifications on 2D DM versus s2D on screening mammography. Methods: This IRB-approved, retrospective, reader study included screening mammograms from 36 women who received screening DBT exams where both 2D DM and s2D images were obtained: 28 screening mammograms that were eventually given BI-RADS category 4 or 5 for amorphous calcifications and 8 BI-RADS category 1 or 2 screening exams. Two rounds of interpretation were conducted with a six-week washout period. Cases were randomized to display either the 2D DM or s2D images, which were then alternated in the second round. Four fellowship-trained breast radiologists determined whether a study merited recall for calcifications. If so, they rated calcification visibility on a scale of 1 to 5. McNemar chi-square tests were conducted to assess differences in recall rates and Wilcoxon signed rank tests were used to examine shifts in visibility. Results: There was no difference in detection rates of amorphous calcifications between 2D DM and s2D, which were 75.9% and 75.0%, respectively ( P = 1.000). Collectively, amorphous calcifications were more visible on s2D than 2D DM, with mean visibility scores of 3.4 versus 3.0, respectively ( P = 0.005). Conclusion: Synthetic 2D did not change identification of amorphous calcifications compared to 2D DM, and readers considered them more visible on average.